Analisis Pembangunan Wilayah Tertinggal di Provinsi Jawa Timur - Satria Wiratama; Herman Cahyo Diartho; Fajar Wahyu Prianto (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
Regional development in disadvantaged areas in an effort to develop the economic potential so as to have competitiveness and boost economic growth. This study aimed to analyze the economic potential and economic performance of the sector in each region lagging East Java Province that could affect GRDP growth and could be a priority in the implementation of regional development. This study uses secondary data in the form GRDP data, with analysis tools Location Quotient and Shift Share Esteban Marquillas, which consist of the data time series during the period from 2009 to 2013, using the GRDP 9 sectors and cross section 4 underdeveloped districts in East Java. The result of this study indicate that the tool Location Quotient, a sector basis contained in the district of Bondowoso is the agricultural sector, a sector basis in Situbondo district is agricultural sector, trade, hotels and restaurants sector, a sector basis in Sampang district is agricultural sector, mining and quarrying sector, a sector basis in Bangkalan district is agricultural sector, construction sector and services sector. From the analysis of the Shift Share Esteban Marquillas sector with competitiveness (competitive) in the Bondowoso district is agricultural sector, manufacturing sector, electricity, gas and water supply sector, construction sector. A competitive sector in Situbondo district is agricultural sector, manufacturing sector, electricity, gas and water supply sector. A competitive sector in Sampang district is agricultural sector, manufacturing sector, trade, hotels and restaurants sector, finance, leasing and corporate services sector, services sector and a competitive sector in Bangkalan district is agricultural sector, manufacturing sector, trade, hotels and restaurants sector, finance, leasing and corporate services sector and services sector. The overall results of these studies demonstrate the implications that the development in disadvantaged areas still not evenly so that it takes the development priorities like as developing the local economy through the use of local resources and community empowerment through increased people's access to education and health services, job creation and the ability to utilize and manage the market.Keywords: Gross Regional Domestic Product, Base Sector and Competitive Advantage